ASSESSMENT OF THE RECEPTIVITY OF THE ENDOMETRIUM TO STEROID HORMONES IN WOMEN WITH CHRONIC ENDOMETRITIS - KіriyaDiana (Scientific Journal of Polonia University, 2023)
Chronic endometritis (CE) is one of the main pathologies that lead to female infertility. Although research on the molecular and biological features of the endometrium in this disease has been conducted for a long time, the problem of studying the morphotype of CE remains relevant. Today, there is no universally accepted panel of immunohistochemical markers that would allow to fully evaluate the status of the endometrium before and after treatment, as well as to evaluate the effectiveness of the therapy. The purpose of our study was to study the features of the expression of markers of estrogen (ER) and progesterone (PR) receptors in order to make a prognosis for the recovery of patients with a possible subsequent pregnancy. For this, 2 research groups were formed using Peipel biopsies of female patients. Group I included cases before treatment, group II – after treatment. During the study, it was found that the criterion for the success of the treatment is a relative decrease of ER- and PR-positive cells both in the stroma (p<0.0001) and in the epithelium of the endometrium (p<0.0001). It was also found, that the expression of PR by the epithelium of the glands shouldn`t exceed 50% (p<0.0001), while for ER the critical level hasn`t been established (p=0.77) and it is possible to judge only the relative decrease in the expression of the marker.